Analisa Sintaksis Tarkib Idlofy dalam Kitab Daqoiq Akhbar karya Imam Abdul Rahman Al Qadli: Analisa Sintaksis Tarkib Idlofy dalam Kitab Daqoiq Akhbar Karya Imam Abdul Rahman Al Qadli - Iis Makhisoh; Muhammad Ridho (STAI At-Tahdzib Rejoagung Ngoro Jombang, 2023)
Abstract: The Book of Daqoiqul Akhbar is a famous book and studied in various Islamic boarding schools. The contents of this book cause a lot of controversy because it discusses matters related to death and the afterlife. the study of the contents of this book related to sentence structure is still rarely done. Additive compound is every two nouns with a partial ratio between them, so the name of the first is called mudhaf and the name of the second is mudhaf ilaih. The rule of the genitive depends on its place in the sentence, and the rule of the genitive is never affixed. Therefore, this study aims to analyze the Tarkib Idhofi or Additive Compound in the book and the meaning contained in the use of this type of sentence structure. This type of research is content analysis research which can also be classified as qualitative research. the results of this research showed that: First, Daqoiqul Akhbar has this type of additive compound of 2053 words, 13 non-pure auxiliary words, and 2040 purely additional ones, either in the singular or in the sentence form. And second, the benefits of the additive compound are two things, (1) for definition and (2) for specialization, there are 1085 words for the benefit of definition and 202 words for the benefit of specialization, 26 words equal in pronunciation and meaning. The meanings included in the additional composition of 2053 words, 1423 words include the meaning